Prospective assessment of subclinical cardiovascular damage and associated factors in liver transplant recipients. (10th November 2020) - Memaran, Nima; Küpper, Claire; Borchert‐Mörlins, Bianca; von Wick, Anika; Bauer, Elena; Jäckel, Elmar; Maasoumy, Benjamin; Vondran, Florian Wolfgang Rudolf; Sugianto, Rizky Indrameikha; von der Born, Jeannine; Schmidt, Bernhard Magnus Wilhelm; Melk, Anette
Summary: Cardiovascular (CV) disease plays a major role after liver transplantation (LT). This prospective study assessed subclinical CV damage after LT by measuring pulse wave velocity (PWV), intima‐media thickness (IMT) and left‐ventricular mass index (LVMI) and characterized associated risk factors. We included 112 patients with a median of 1.8 years after LT (q1–q3 0.9–9.2). Fifty‐three percent ( n = 59) of patients had ≥2 annual assessments (median follow‐up 1.6 years, q1–q3 1.1–2.0), with a total of 195 assessments. We found increased PWV (indicating arteriosclerosis) in 16% ( n = 17), elevated IMT in 5% ( n = 5; indicating atherosclerosis) and increased LVMI in 25% ( n = 24; indicating left‐ventricular hypertrophy). A linear mixed model analysis using all 195 assessments revealed that higher age and systolic blood pressure (BP) were associated with higher PWV (β = 0.069, P < 0.001 and β = 0.022, P = 0.005) and higher IMT (β = 0.005, P < 0.001 and β = 0.001, P = 0.029), while higher body mass index was associated with higher IMT (β = 0.004, P = 0.023). Higher systolic BP (β = 0.200, P = 0.034), male sex (β = 8.847, P = 0.031) and lower glomerular filtration rate (β = −0.288, P < 0.001) were associated with higher LVMI. Our data highlight not only the rate of subclinical CV damage in LT patients, but also the impact of classical CV risk factors (such as BP and body mass index) which outweighed LT‐related factors. These modifiable risk factors are suitable targets for interventions to reduce CV morbidity in LT patients.